KESEDIAAN MASYARAKAT MENERIMA PEMBAYARAN JASA LINGKUNGAN AIR: KASUS DAS WAY SEMAKA KABUPATEN TANGGAMUS - Susni Herwanti (Gorontalo Journal of Forestry Research, 2020)
ABSTRAKPembayaran jasa lingkungan (PJL) merupakan salah satu skema pemberian insentif dalam upaya mencegah kerusakan hulu Daerah Aliran Sungai (DAS) Way Semaka di Kawasan Hutan Lindung Register 19. Kerusakan hulu DAS ini menyebabkan pasokan air yang dimanfaatkan oleh pengguna air di daerah hilir terganggu. Penelitian ini bertujuan untuk menganalisis kesediaan masyarakat menerima (willingness to accept/WTA) atas pembayaran jasa lingkungan air. Data dianalisis secara kuantitatif terhadap 30 orang sampel responden masyarakat sekitar Hutan Lindung Register 39. Pengambilan sampel dilakukan secara acak. Hasil penelitian  menunjukkan bahwa semua responden bersedia dibayar atas upaya konservasi DAS melalui penanaman dan pemeliharaan pohon dalam kawasan hutan yaitu rata-rata Rp14.000 per pohon. Hal ini didasarkan oleh pengorbanan yang dikeluarkan responden dari segi waktu, biaya dan tenaga dalam upaya konservasi tersebut. Penerapan PJL ini perlu dukungan Pemerintah dalam hal ini Kesatuan Pengelolaan Hutan Lindung (KPHL) Kotaagung Utara selaku pengelola di tingkat tapak agar memfasilitasi terselenggaranya mekanisme PJL hulu-hilir di sekitar kawasan hutan lindung sebagai salah satu solusi perbaikan hulu DAS Way Semaka.  Kata kunci: pembayaran jasa lingkungan; DAS Way Semaka; Willingness to Accept; hutan lindung ABSTRACTPayment of environmental services (PES) is one of the mechanisms considered to be able to solve the hydrological problem in Way Semaka Watershed (DAS) which is one of the watersheds used by the downstream community for daily necessities and agricultural business. Currently, Way Semaka Watershed condition is physically damaged one of them because the protected forest area surrounding the watershed is damaged. Whereas protected forests play a very important role in regulating the water system, prevent erosion, produce oxygen and so on. This study aims to analyze the willingness to accept community (WTA) around protected forest area register 39 upstream through PES mechanism in order to restore downstream watershed condition. Samples were taken as many as 30 community respondents around the forest register 39 at random. Data were analyzed qualitatively and quantitatively. The results showed that all respondents were willing to be paid for planting and maintaining trees in forest areas. The estimated average WTA value is Rp 14,000 per tree. According to the respondents, the willingness to accept this community must take into account the time, cost and energy in planting and maintaining the tree, especially the topography condition of the forest area is relatively flat. Therefore, the government in this case Protection Forest Management Unit (KPHL) Kotaagung Utara need to support the implementation of mechanisms PES in the area around the Way Semaka Watershed in order to solve the problem of hydrology and the welfare of the community around the protected forest by acting as facilitator to the downstream user community.Keywords: Payment of environmental services; protected forest area; Way Semaka Watershed; Willingness to Accept